Accountability of the 2020 Village Fund Allocation Management (Alokasi Dana Kampung) in Arul Pertik Village, Central Aceh Regency, Indonesia - Hasan Basri; Muhsin Efendi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2021)
In Indonesia, the central government provides Village Fund Allocation (VFA) to improve welfares in villages. This process, with its regulation, is known as alokasi dana kampung in Aceh province. However, irrespective of this implementation, the community's welfare is still not met, leading to the inability to meet management accountability. This study was carried out in Arul Pertik Village, using the qualitative method with a descriptive approach. The result showed that the VFA management team is open to accepting suggestions and advice during the planning and implementation process. VFA management in Arul Pertik tends to respect community participation, as seen from the number of participants in the development and implementation of the physical realization process. This is also in addition to the accountability report (LPJ), irrespective of the technical obstacles in the report. In conclusion, although the Management of Village Fund Allocation is quite good, it needs more extra guidance and supervision from the local government and the community. Keywords: Accountability; Village fund allocation; Village Fund Management, Arul Pertik Village.